Jane's crisis communications handbook - Fernandez, Louie; Merzer, Martin (Coulsdon, Surrey, UK ; Alexandria, VA : Jane's Information Group, 2003)
This book is designed to assist organizations and their employees to cooperate with the media and inform, calm, and direct their stakeholders and public during any emergency.
Strategic overview -- Pre-incident media relations -- Planning procedures -- Response procedures checklist -- Gathering and verifying information -- Messages and strategy -- Engaging key stakeholders -- Working with the media -- Post-incident management -- Appendices.
http://www.amazon.com/Janes-Crisis-Communications-Handbook-Fernandez/dp/0710625960/ref=sr_1_1?s=books&ie=UTF8&qid=1411714890&sr=1-1&keywords=0710625960
Keywords: Crisis management; Emergency communication systems; Emergency management; Mass media; Public relations